Bateria montreal-toulouse de avaliação da linguagem : evidências de validade e de fidedignidade com adultos saudáveis e com lesão cerebral unilateral com e sem afasia - Pagliarin, Karina Carlesso (2013)
The Montreal-Toulouse Language Assessment Battery (MTL-BR) has been adapted, extensively revised and redesigned from French to Brazilian Portuguese to assess components of spoken and written language, praxis and mathematical ability after brain injury. The aim of this thesis was to collect evidence toward the validity and reliability of this instrument, verifying the role of age, education, aphasia and unilateral brain injury on performance in the MTL-BR Battery through three empirical studies. The first study aimed at analyzing the effects of age and education on the performance of 463 healthy adults in the MTL-BR, so as to contribute to normative data. Mean group scores were compared using a two-way ANOVA with post-hoc Bonferroni tests. Descriptive analyses for the normative data were also conducted. The second study looked for evidence toward the construct/convergent validity and reliability of the instrument in clinical and non-clinical adults. Test-retest reliability (correlation and repeated measure) and internal consistency (Cronbach s alpha) were analyzed. Validity was analyzed by correlating performance across subtests. The third study investigated criterion-related validity. One hundred and four adults divided into clinical (with three groups: left hemisphere damaged LHD with aphasia, LHD without aphasia and right hemisphere damaged -RHD) and control (healthy adults) groups participated in this study. Performance was compared between groups with a one-way ANCOVA with depression as a covariate, and post-hoc Bonferroni tests. Both education and age influenced performance in the MTL-BR Battery, but the effect of education was more important. The MTL-BR Battery presented adequate indicators of reliability and validity, adequate internal reliability and testretest correlations, as well as satisfactory correlations with similar instruments. As expected, patients with aphasia had lower scores than controls on all tasks except in the spoken word comprehension subtask. The LHD group without aphasia underperformed the control group only in phonological verbal fluency. There were no significant differences in any subtasks between LHD patients without aphasia and RHD, or RHD versus controls. The findings of all three studies suggested that the MTL-BR has adequate external validity. The data obtained contribute to clinical assessment of aphasia in Brazil and to reflections upon the implications of linguistic-communicative changes on diagnosis and rehabilitation.